2010
DOI: 10.1158/0008-5472.can-09-4674
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Beauty–Mediated Somatic Mutagenesis Implicates CSF1 in the Formation of High-Grade Astrocytomas

Abstract: The Sleeping Beauty (SB) transposon system has been used as an insertional mutagenesis tool to identify novel cancer genes. To identify glioma-associated genes, we evaluated tumor formation in the brain tissue from 117 transgenic mice that had undergone constitutive SB-mediated transposition. Upon analysis, 21 samples (18%) contained neoplastic tissue with features of high-grade astrocytomas. These tumors expressed glial markers and were histologically similar to human glioma. Genomic DNA from SB-induced astro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…This study also demonstrated that CSF-1 expression correlated with the increased presence of macro phages bearing markers that are associated with the so-called "M2 phenotype," which are believed to be one of the critical subpopulations of macrophages involved in tumor progression (6). In addition, a recent study used the Sleeping Beauty transposon mutagenesis technique in the brains of whole animals to screen for novel genes associated with glioma oncogenesis (23). It was discovered that >60% of the highgrade astro cytoma occurrence was a result of transposon-mediated enhanced expression of the Csf-1 gene.…”
Section: Resultsmentioning
confidence: 79%
“…This study also demonstrated that CSF-1 expression correlated with the increased presence of macro phages bearing markers that are associated with the so-called "M2 phenotype," which are believed to be one of the critical subpopulations of macrophages involved in tumor progression (6). In addition, a recent study used the Sleeping Beauty transposon mutagenesis technique in the brains of whole animals to screen for novel genes associated with glioma oncogenesis (23). It was discovered that >60% of the highgrade astro cytoma occurrence was a result of transposon-mediated enhanced expression of the Csf-1 gene.…”
Section: Resultsmentioning
confidence: 79%
“…1B), was selected for further investigation given 1) its well suggested role in the development and progression of tumors, including glioma (24,25); 2) its influence upon survival, proliferation, and differentiation of macrophages/microglial cells, which are present in abundance in the glioma microenvironment (26,27); and 3) the expression of MCSF receptor (MCSFR) only in microglial cells and not in glioma cells (28), suggesting that glioma cell-secreted MCSF may function through stromal cells and be one key determinant of glioma-stromal cell interactions underlying glioma progression. MCSF transcript levels were up-regulated in GBM, compared with normal brain tissue samples, in our cohort and three more cohorts, namely TCGA, REMBRANDT, and GSE22866 (Fig.…”
Section: Cytokine Profiling Identifies Elevated Levels Of Serum Mcsf mentioning
confidence: 99%
“…M-CSFR inhibition abrogates glioma progression by inhibiting the pro-tumor activation of TAMs (25). Although there have been a number of research studies regarding M-CSF production from glioma cells (26)(27)(28), to the best of our knowledge, there is no published research assessing M-CSFR expression in glioma cells, other than a previous study that reported the activation of M-CSFR in both glioma cells and TAMs in human glioma samples (8). The observations indicated that M-CSFR expression in cultured glioma cell lines is markedly lower than that in macrophages, and may suggest that M-CSFR expression in glioma cells may not be of particular interest for further research.…”
Section: Discussionmentioning
confidence: 99%